Cotidiano e experiência no trabalho rural da cana-de-açúcar em Lagoa da Prata, Minas Gerais: as trajetórias de vida de Dona Alzira e Dimas - Marcela Sobreira Silva (2011)
The production of sugar cane in Brazil is released as a promise to the countrys progress and investment in this production has been increasing, especially in Minas Gerais. The initiatives for this investment are expanding cane fields under the endorsement of a history that reproduces and allies the sugar canes production and the economic and social development. This history is told in accordance with the governmental and economic interests and summarizes the entire production of sugar cane in political articulations of important events. This history doesnt show the rural worker human life present in the cane fields, maintainer of this production. While the official history of cane openly proclaims economic advancement and projects Brazil on the international scene, stories of life and work remain hidden. Giventhis consideration, this research proposes a method based on psychosociology and clinical sociology: we collect life trajectories crossed by the sugar cane production and reach out to those who actually can say and express the meaning of this production process. Dimas e Alzira, the rural workers involved in the sugar cane production during the 1970s and 1980s, reports the oppression and the bad conditions of the work in sugar fields. The exhaustion on worker health and on the environment is evident. But, the trajectories of these rural workers are also marked by the political engagement. This fact certifies that the real story is contrary to the official history.